The Mediation Effect of Financial Performance on CSR Disclosure and GCG on Firm Value during the Pandemic - Quranni, Nazillatul Ismi; Arifah, Dista Amalia (Universitas Pamulang, 2024)
This research aims to determine the effect of CSR Disclosure and CGC with profitability as a mediating variable on company value. This research was conducted to see how CSR and GCG affect company value during the pandemic. To test this variable, researchers used a population of all companies registered with the Kompas100 companies listed on the Indonesia Stock Exchange (BEI) in 2020. Using purposive sampling, the total sample taken was 86 companies. Hypothesis testing is carried out using descriptive analysis methods with multiple linear regression techniques. The research results show that CSR disclosure does not significantly affect financial performance and company value. The results also show that GCG positively and significantly affects financial performance and company value. Financial performance also influences company value but cannot mediate CSR Disclosure and GCG on company value.